NbCycB2 represses Nbwo activity via a negative feedback loop in tobacco trichome development. (28th January 2020) - Wu, Min-Liang; Cui, Yu-Chao; Ge, Li; Cui, Li-Peng; Xu, Zhi-Chao; Zhang, Hong-Ying; Wang, Zhao-Jun; Zhou, Dan; Wu, Shuang; Chen, Liang; Cui, Hong
Abstract : NbCycB2 is specifically expressed in trichomes of Nicotiana benthamiana and inhibits their formation by repressing Nbwo activity via a negative feedback loop. Abstract: The transcription factor Woolly ( Wo ) and its downstream gene CycB2 have been shown to regulate trichome development in tomato ( Solanum lycopersicum ). It has been demonstrated that only the gain-of-function allele of Slwo ( SlWo V, the Slwo woolly motif mutant allele) can increase the trichome density; however, it remains unclear why the two alleles function differently in trichome development. In this study, we used Nicotiana benthamiana as a model and cloned the homologues of Slwo and SlCycB2 (named Nbwo and NbCycB2 ). We also constructed a Nbwo gain-of-function allele with the same mutation site as SlWo V (named NbWo V ). We found that both Nbwo and NbWo V directly regulate NbCycB2 and their own expression by binding to the promoter of NbCycB2 and their own genomic sequences. As form of a feedback regulation, NbCycB2 negatively regulates trichome formation by repressing Nbwo activity at the protein level. We also found that mutations in the Nbwo woolly motif can prevent repression of NbWo V by NbCycB2, which results in a significant increase in the amount of active Nbwo proteins and in increases in trichome density and the number of branches. Our results reveal a novel reciprocal regulation mechanism between NbCycB2 and Nbwo during trichome formation in N. benthamiana .